Experiences and Opinions of Special Education Teachers Regarding the Use of Technology - Evgin Çay; Ahmet Yıkmış; Canan Sola Özgüç (Anı Publishing, 2020)
This study aims to determine the experiences and opinions of special education teachers working in a special education school regarding the use of assistive technology. A total of eight teachers, one male and seven female, working in a special education vocational school have participated in the study. The research is based on phenomenological research design, and the data has been collected with semi-structured interview technique. The data obtained from the interviews were analyzed using the content analysis technique with NVivo 10 program. The findings have revealed information on the teachers' use of assistive technology and the areas it is used in, their access to technological tools, the benefits of using assistive technology for students, teachers and parents, the difficulties those teachers have in terms of using assistive technology, and their opinions and suggestions regarding the use of assistive technology. The findings are discussed considering the teachers' opportunities and suggestions as of the current year in which the study was conducted.